The Application of Liquid Organic Fertilizer Increasing the Productivity of Pakchoy Plants (Brassica rapa L.) in Soil with Low Nutrient Content - Isnainy, Dyon Rahman; Asnur, Paranita; Istiqlal, Muhammad Ridha Alfarabi; Kalsum, Ummu (Jurnal Biologi Tropis, 2025)
Organic farming plays a very important role in maintaining environmental balance because it can reduce the use of harmful synthetic chemicals. This LOF is considered capable of enhancing soil fertility and supporting plant growth, while simultaneously reducing waste from the aquaculture sector. This study aims to evaluate the effect of liquid organic fertilizer (LOF) from catfish pond wastewater on the productivity of pakcoy (Brassica rapa L.) plants grown in soil with low nutrient content. The research was conducted in the experimental field of Universitas Gunadarma, East Jakarta, using 18 combinations of POC treatments with various concentrations and five varieties of pakcoy. Data were analyzed using the F-test to determine the overall treatment effect, followed by the Duncan Multiple Range Test (DMRT) at a 5% significance level to compare between treatments. The research results show that the application of POC from catfish pond wastewater has a positive effect on the growth of pakcoy compared to the control. A POC concentration of 0.75 ml/L yielded the best results in most parameters, including plant height, number of leaves, as well as leaf length and width. Although not all treatment combinations yielded significant results, the use of POC generally shows great potential in increasing the productivity of pakcoy plants. POC from catfish pond wastewater is not only effective as an organic fertilizer but also supports sustainable agriculture by reducing the negative impact of aquaculture waste on the environment. This research recommends POC as an environmentally friendly fertilizer alternative to improve agricultural yields, especially in areas with low nutrient content, through gradual soil quality improvement.